2015
DOI: 10.1111/joor.12312
|View full text |Cite
|
Sign up to set email alerts
|

Effortful swallow enhances vertical hyolaryngeal movement and prolongs duration after maximal excursion

Abstract: Effortful swallowing (EFS) is a common compensatory swallowing manoeuver for dysphagia patients. We investigated the influence of EFS on temporal and spatial characteristics of the movements of the hyoid bone, larynx and epiglottis in healthy subjects. A total of 41 volunteers swallowed 10 mL of diluted barium solution using two swallowing strategies: usual and effortful swallowing (USS and EFS). The motions of the hyoid bone, larynx and epiglottis were tracked using frame-by-frame kinematic motion analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
0
31
0
2
Order By: Relevance
“…As a result, a compensatory technique was initially introduced for the purpose of improving the clearance of vallecular residues in the pharyngeal phase (Jang et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…As a result, a compensatory technique was initially introduced for the purpose of improving the clearance of vallecular residues in the pharyngeal phase (Jang et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Jang et al . () reported the effects of EST on hyolaryngeal movement in healthy adults. EST proved to be more effective for the anterior–superior movements of the hyolaryngeal than for normal swallowing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that hyoid movement is affected by bolus size3,4 and viscosity, 5 as well as by swallowing manoeuvres such as effortful swallowing 22. In those tasks, the correlation between the LM value and the y-axis displacement was stronger than that with the x-axis displacement.…”
mentioning
confidence: 87%
“…Due to population aging and the increase on the number of people affected by diseases that lead to swallowing alterations, the early identification and management of dysphagia must be a priority to reduce the risk of severe complications and improve the results with vulnerable populations (2) . Besides using adaptations at the moment of oral intake, it has been suggested a variety of exercise protocols to improve the swallowing capacity aiming at larger range of movement (3) , increase at the swallowing effort (4)(5)(6) and sensorial system impulse (7) . Among them are tongue-hold (8,9) , Shaker exercise (10) , counter-resistance exercise with head lowered (11) , tongue exercises (12) , Iowa Oral Performance Instrument -IOPI (13) , etc.…”
Section: Introductionmentioning
confidence: 99%